2012
DOI: 10.3917/lhs.183.0207
|View full text |Cite
|
Sign up to set email alerts
|

Des agriculteurs contre le marché ? Itinéraire d'un mode alternatif de commercialisation des fruits et légumes

Abstract: Distribution électronique Cairn.info pour Association pour la Recherche de Synthèse en Sciences Humaines (ARSSH). © Association pour la Recherche de Synthèse en Sciences Humaines (ARSSH). Tous droits réservés pour tous pays.La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 4 publications
0
5
0
2
Order By: Relevance
“…For example, some AMAP maintain the participatory and collective character of the decisions between producers and consumers. Others have moved away from them and have adopted less restrictive arrangements for exchange, due to the development of competing forms of shopping carts , expanding consumer profiles or commercial success (Lanciano and Saleilles, 2011; Samak, 2012).…”
Section: Analysis Of the Literature: Paradoxical Territorial Managemementioning
confidence: 99%
See 2 more Smart Citations
“…For example, some AMAP maintain the participatory and collective character of the decisions between producers and consumers. Others have moved away from them and have adopted less restrictive arrangements for exchange, due to the development of competing forms of shopping carts , expanding consumer profiles or commercial success (Lanciano and Saleilles, 2011; Samak, 2012).…”
Section: Analysis Of the Literature: Paradoxical Territorial Managemementioning
confidence: 99%
“…In quantitative terms, conventional agriculture is obviously dominant; however, in qualitative terms, consumers believe that localised agrifood systems (LAFS) 3 offer more trusted brands and guarantees of quality in the wake of various food scandals (Blanc, 2013; Dubuisson-Quellier, 2008). Yet, proportionately, most of these are located in peri-urban areas (Samak, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Les premiers travaux académiques, anglo-saxons, à partir des années 1990, y verront autant de systèmes alternatifs aux circuits conventionnels. Or, toutes modalités confondues 2 , les circuits courts relèveraient davantage d'une (Le Velly et Dubuisson-Quellier, 2008 ;Olivier et Coquart, 2010 ;Samak, 2012).…”
Section: U T O P I Q U E S a L L I A N C E S ? L A C O N S T R U C T unclassified
“…Recent research in economic sociology showed that involvement through subscriptions to fresh produce baskets is one of the dimensions of the specific trade relationship set up in CSA, but not always sufficient to build a community, especially when CSA/CSF are getting bigger or offer a "close-tomarket" nature, through a choice of products, type of contract, convenient delivery time, etc. (Rippol 2013;Samak 2012).…”
Section: Introductionmentioning
confidence: 99%